Pengaruh Konseling Teknik Tazkiyatun Nafs dalam Mereduksi Kegelisahan Lansia - Irman, Irman; Dasril, Dasril; Silvianetri, Silvianetri; Yeni, Putri (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
The Effect of Tazkiyatun Nafs Counseling Techniques in Reducing Anxiety in the Elderly. Anxiety is a dominant problem experienced by the elderly which has a negative effect on the physical and psychological. One intervention that is considered appropriate to reduce anxiety is through counseling the tazkiyatun nafs technique. This study was conducted to determine the effect of the tazkiyatun nafs counseling technique in reducing the anxiety of the elderly. The approach used is an experiment with a pretest & pottest control group design. The population of this study was the elderly at the Tresna Werda Kasih Sayang Ibu Batusangkar Social Home, with a sample of 16 people taken at random. Collecting data using an anxiety scale, data analysis through independent t test. Research result; there is a difference in the increase in anxiety given the tazkiyatun nafs counseling intervention compared to the elderly who received information services. Tazkiyatun nafs counseling has a significant effect in reducing anxiety. It is recommended for nursing homes and professionals to be able to use the tazkiyatun nafs technique of counseling in dealing with elderly anxiety problems, as well as additional information on variations in counseling techniques. Keywords: Counseling, Tazkiyatun Nafs, Anxiety